Pemikiran Hadith Dr Abdul Hayei Abdul Sukor: The thoughts of Hadith by Dr Abdul Hayei Abdul Sukor - Abd Razzak, Monika @ Munirah; Ab Rahim, Nik Mohd Zaim (Al-Basirah Journal, 2022)
Abdul Hayei Abdul Sukor is a national hadith figure who has contributed many of his ideas in the field of hadith through his writing. He was an active participant who shared his thoughts and comments on his understanding of hadith. This article depicts Abdul Hayei Abdul Sukor’s hadith thoughts through the works he created. To collect data, inductive, deductive, and comparative methods were used, while inductive, deductive, and comparative methods were used for data analysis. The analysis focuses on Abdul Hayei Abdul Sukor’s commentary on hadith thought in some of his works from the perspective of narration of alhadith, dirayah hadith, and sharh hadith. According to the findings of the analysis, Abdul Hayei Abdul Sukor emphasised the use of authentic hadiths in his arguments. He was one of the figures who fought for the use of authentic and accurate hadith while avoiding the use of da’if hadith in debate. He is also adamant about using hadith da’if in matters of fada’il a’mal, though this is not the foundation of his hadith thinking.